Smallest organocatalyst in highly enantioselective direct aldol reaction in wet solvent-free conditions - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (RSC Advances, 2014)
The catalytic efficacy of the smallest organocatalyst, L-proline hydrazide, prepared from a cheaply available natural amino acid, such as L-proline, was studied for the direct asymmetric aldol reaction of various ketones with aromatic aldehydes at room temperature in the presence of several acid additives. A loading of 10 mol% of catalyst 1 and p-toluenesulphonic acid as an additive was employed in this reaction, and good yields (up to 99%) with high anti/syn diastereoselectivities (up to 95 : 5) and enantioselectivities (up to >99.9%) were achieved in aqueous media.